Evaluación del efecto antibacteriano, in vitro, del extracto etanolico caesalpinia spinosa (Tara) en cepas de Staphylococcus aureus atcc 25923 - Tisnado Cueva, Doris Angelica; Hurtado Guía, Eddy Jesús (Universidad Privada de Huancayo Franklin Roosevelt, 2021)
Esta investigación determino el efecto antibacteriano de Caesalpinia spinosa (Tara) en cepas de Staphylococcus aureus identificando sus metabolitos secundarios, se registraron todos los procedimientos en fichas de observación donde se anotó todos los procedimientos establecidos. Nuestro objetivo fue determinar que concentración tiene mayor similitud a nuestro control positivo, se realizaron soluciones en porcentajes de12.5%, 25%, 50%, 75% y 100%. Metodología se realizaron pruebas de tamizaje, cuantificación de taninos- flavonoides, cromatografía en capa fina para flavonoides y alcaloides. Resultados Se demostró que tiene efecto antibacteriano ante las cepas de Staphylococcus aureus

This research determined the antibacterial effect of Caesalpinia spinosa (Tara) on Staphylococcus aureus strains by identifying its secondary metabolites, all procedures were recorded in observation sheets where all established procedures were noted. Our objective was to determine which concentration has the greatest similarity to our positive control, solutions were made in percentages of 12.5%, 25%, 50%, 75% and 100%. Methodology Screening tests were performed, quantification of tannins-flavonoids, thin layer chromatography for flavonoids and alkaloids. Results It was demonstrated that it has an antibacterial effect against Staphylococcus aureus strains
Evaluation of the antibacterial effect, in vitro, of the ethanol extract caesalpinia spinosa (Tara) in strains of Staphylococcus aureus atcc 25923
Keywords: Caesalpinia spinosa; Efecto antibacteriano; Staphylococcus aureus; Metabolitos secundarios; https://purl.org/pe-repo/ocde/ford#3.01.05